Polymer derived ZrO2 reinforced SiC-ZrB2 polycrystalline fiber. Issue 9 (August 2022) - Zhang, Peng; Zheng, Zhibing; Zhuang, Kaiwen; Sun, Chenxi; Yu, Zhaoju; Chen, Jiangxi; He, Guomei
Abstract: Most polycrystalline SiC-based fibers were prepared at a sintering temperature higher than 1600 °C. In this work, a ZrO2 reinforced SiC-ZrB2 polycrystalline fiber was prepared at 1400 °C via the polymer-derived ceramic method from a new Zr- and B-containing polycarbosilane. The morphology and microstructure of the polycrystalline nanocomposite fiber were studied using XRD, XPS, EDS, SEM, and TEM. The results showed that t -ZrO2 was formed at relatively lower temperature (<1000 °C). The most interesting result is that the polycrystalline nanocomposite SiC-ZrB2 was generated after heat-treatment at 1400 °C, producing an excellent ZrO2 reinforced SiC-ZrB2 polycrystalline fiber. The present study provides a novel strategy for the fabrication of SiC-based polycrystalline fiber at a relatively low temperature.